Penerapan Model Problem Based Learning Untuk Meningkatkan Kreativitas Berpikir dalam Pembelajaran Tematik di Kelas V SDN Jomerto 2 Patrang - Putri, Risanatih Maulida; Prayogo, Muhammad Suwignyo (Pendidikan Islam Pascasarjana IAIN Jember, 2022)
The 2013 curriculum was one of the answers to previous curriculum changes. The change can be seen in learning activities that use a scientific approach with a combination of thematic learning. Mix in several subject matter into one theme. One way to improve the quality of learning, student-centered learning. Therefore, teachers are the spearhead in stimulating students to play an active role. This can be done by creating an effective learning activity process. One of the learning models that can stimulate students to play an active role in critical thinking is the Problem Based Learning (PBL) learning model in designing learning implementation plans. The type of method used in this writing is to use qualitative research. The observations made refer to the type of field research